Quantifying the drivers and predictability of seasonal changes in African fire - Yan Yu (Nature Portfolio, 2020)
Fire is an important component of many African ecosystems, but prediction of fire activity is challenging. Here, the authors use a statistical framework to assess the seasonal environmental drivers of African fire, which allow for a better prediction of fire activity.